BETWEEN SUSTAINABILITY AND REGULATION: LEGAL PERSPECTIVES ON THE IMPORT AND SALE OF SECOND-HAND CLOTHING IN INDONESIA - Wafiya Wafiya (Adisam Publisher, 2024)
This article explored the legal challenges surrounding the import and sale of second-hand clothing in Indonesia, focusing on the intersection between sustainability goals and regulatory frameworks. The research aimed to analyze the tension between the environmental benefits of reuse practices and the strict prohibition stipulated in Indonesian trade regulations, particularly Article 47 paragraph (1) of Regulation of the Minister of Trade No. 40 of 2022. Employing normative juridical methods supported by statute and conceptual approaches, the study investigated both domestic and international legal norms, including WTO principles and sustainable development goals (SDGs). The findings revealed a legal paradox: while importing second-hand clothing supported circular economy practices and reduced textile waste, it was simultaneously deemed illegal under the prevailing laws, creating regulatory inconsistency. The article argued for a more balanced legal reform that aligned trade policy with sustainability imperatives, promoting legal certainty and environmental responsibility. This research contributed to the broader discourse on green lawmaking in developing countries and underscored the importance of harmonizing domestic regulations with global sustainability commitments.